International legal combating trafficking in women from human rights and gender perspective - Emelyanovich, Olga V. (Journal of the Belarusian State University. International Relations, 2020)
The article considers specific issues regarding international legal combating trafficking in women from human rights and gender perspective and contains its definition. The author determines that international legal combating trafficking in women has a gender specificity. This brings the vulnerable position of women into focus in the process of development and adoption of measures to prevent trafficking, as well as the provision of assistance to victims and also envisages the involvement of non-governmental organizations. The author proposes a periodization of international legal framework in combating trafficking given the peculiarities of its foundation and evolution. Specific anti-trafficking efforts of the United Nations, Organization for Security and Co-operation in Europe, Commonwealth of Independent States are also considered. Special attention is paid to anti-trafficking activities of the Republic of Belarus.
Keywords: international legal combating trafficking in women; gender; human rights; due diligence standard